Emotional intelligence and job satisfaction among occupational therapists in Malaysia / Ruzana Ramli and Mohd Suleiman Murad - Ramli, Ruzana; Murad, Mohd Suleiman (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
The emotional intelligence plays important role in achieving job satisfaction. The relationship of emotional intelligence and job satisfaction by proving theories of emotional intelligence reveals that individual who have satisfactory and interpersonal competencies can properly handle their emotions as well as the others' emotion to cope with environmental challenges. This study aims to investigate relationship between emotional intelligence and job performance among occupational therapists in Malaysia. Wong and Law Emotional Intelligence Scale and job Satisfaction Scale questionnaires were used in this cross-sectional study involving 63 occupational therapists in Malaysia. The study found a significant positive relationship between emotional intelligence and job satisfaction. Regression analysis showed that four domains of emotional intelligence including self-emotional, others' emotional appraisal, regulation of emotional and use of emotion predicted the job satisfaction. Results also showed that level of emotional intelligence significantly affected the job satisfaction of occupational therapists. However, there is no significant difference between male and female therapists regarding the level of emotional intelligence. The present study revealed an association between emotional intelligence and job satisfaction among occupational therapists in Malaysia. Therefore, emotional intelligence is important in terms of its relationship with job satisfaction. Future efforts for selection boards for occupational therapists across the state as well as in the Centre are advised to keep in mind the level of emotional intelligence of the candidates who tend to be selected for the entitled job and position.